Cervical tumoral calcinosis with secondary hyperparathyroidism in a chronic hemodialysis patient. Issue 3 (16th October 2012) - Sunder, Sham; Verma, Himanshu; Venkataramanan, Krishnamoorthy
Abstract Tumoral calcinosis is an uncommon and severe complication of chronic renal failure. It is generally associated with the presence of a high‐serum calcium‐and‐phosphorus product. We report here a case of a patient on maintenance hemodialysis who presented with progressively increasing, solitary, tumor‐like swelling over the nape of the neck. A 50‐year‐old female on thrice weekly maintenance hemodialysis for the last 3 years presented with a small swelling over the nape of the neck that had been progressively increasing over the last 1 year to cricket ball size. The patient was investigated and diagnosed as having tumoral calcinosis. The metastatic calcification occurring in the patient was most likely related to high calcium × phosphate product with coexistent secondary hyperparathyroidism possibly aggravated by vitamin D therapy. The patient was treated with withdrawal of vitamin D therapy, strict control of serum phosphate levels with noncalcemic phosphate binders, and subtotal parathyroidectomy. The neck swelling started decreasing in size after 2 months of parathyroidectomy and there was marked clinical improvement with drop in serum parathormone levels, over a period of 6 months. After 2 years of parathyroidectomy, the neck swelling again started increasing in size with increase in serum parathormone levels. The patient was treated with cinacalcet and the neck swelling gradually decreased in size along with control of serum parathormone and phosphate levels.